Building A Model in Collaborative Approach: IDSurvey's Role as a Corporate Decarbonization Consultant - Misbahudin Aidy; Chandra Wijaya (International Journal of Science and Society, 2023)
Carbon trading and carbon markets are critical mechanisms in global efforts to address the impacts of climate change by reducing greenhouse gas emissions. These initiatives incentivize businesses and countries to limit carbon dioxide (CO2) and other greenhouse gas emissions. This study analyzes the role of IDSurvey as a company that provides decarbonization technical assistance or decarbonization consultants. Using Soft Systems Methodology (SSM), this study examines IDSurvey's collaborative innovation in building the company's capacity to reduce greenhouse gas emissions towards the Net Zero Emissions (NZE) 2060 target. The research illustrates the innovation cycle in the public sector, highlighting idea generation, selection, implementation, and dissemination as critical stages in driving collaborative solutions for mitigation towards NZE. The results show that IDSurvey has a strategic role and position as a consulting company to help corporations benefit from carbon pricing by going through essential stages until the realization of emission reductions and the potential added value that can be obtained from carbon trading through the Carbon Exchange. Carbon pricing is a practice of the "polluters-pay-principle," so anyone who emits carbon emissions must pay compensation for the pollution released, especially for industries or businesses. This article highlights the importance of a systemic and collaborative approach to decarbonization, which places IDSurvey in a critical and global context.